Highlights of eosinophilic chronic rhinosinusitis with nasal polyps in definition, prognosis, and advancement - Lou, Hongfei (Int Forum Allergy Rhinol, 2018)
BACKGROUND: Tissue eosinophils are characteristic of inflammation in most but not all patients with chronic rhinosinusitis with nasal polyps (CRSwNP) and may be useful for defining subgroups and making treatment choices. However, no consistent diagnostic criteria for CRSwNP with eosinophilic inflammation have been established. METHODS: Related literature review was performed and current developments in the diagnosis of eosinophilic CRSwNP were summarized. Details in histopathology, definition of tissue eosinophilia, eosinophil as an indicator of disease recurrence, eosinophilic shift, and related biomarkers in CRSwNP are included in this review article. RESULTS: Mucosal eosinophilia exhibits significant geographic and ethnic differences and may increase over time. Tissue eosinophilia can be defined using a cutoff value based on reference values from healthy mucosa, but typical disease‐specific values should also be employed to increase sensitivity and specificity for clinical use. Recent developments highlight the diagnostic criteria for eosinophilic CRSwNP based on cluster analysis, which were also associated with clinical outcomes. Additionally, some promising eosinophil‐relevant biomarkers, such as eosinophilic cation protein and interleukin 5 (IL‐5), may be clinically applied as diagnostic or predictive tools for CRSwNP in the future. CONCLUSION: Sinonasal tissue eosinophilia is present in a majority of CRSwNP patients but is currently more common in the West than in the East. Cutoff values of eosinophils as the diagnostic criteria of eosinophilic CRSwNP are subject to change with geographic and ethnic differences over time. It will be important to identify validated eosinophil‐related biomarkers in different continents/countries for future research and for the introduction of precision medicine.